A comparison of quality of life indicators during two complementary interventions: adaptive gardening and adaptive riding for people with dementia - Rebecca Lassell; Wendy Wood; Arlene A. Schmid; Jennifer E. Cross (Elsevier, 2021)
Objectives: We sought to provide a fine-grain description and comparison of how people living with dementia responded to adaptive gardening and adaptive riding through durations of their observed participation and emotional well-being, two dimensions of quality of life. Design: A descriptive case study design enabled in-depth description and comparison of participation and emotional well-being, two quality of life indicators, observed during four videotaped sessions of adaptive gardening and adaptive riding. Interventions: Eight people living with dementia self-selected into one of two complementary interventions, community-based adaptive gardening (n = 4) or adaptive riding (n = 4), in Northern Colorado. Both occurred for hour-long, weekly sessions for eight-weeks. Outcome Measure: Durations of observed quality of life indicators of participation and apparent affect were documented using a modified version of the Activity-in-Context-in-Time on 31 hours of videotaped data. Durations for each quality of life indicator were averaged per participant and aggregated by group for comparison using a Wilcoxon Mann-Whitney U test Results: Both interventions supported emotional well-being and participation. Longer durations of active participation were observed during adaptive riding with significantly higher durations of complex active participation (U = 16, p= 0.029). Conclusion: Both interventions supported quality of life and merit continued development. Adaptive riding appeared to support longer durations of active participation with more complex forms when compared to adaptive gardening. Findings can inform healthcare providers' recommendations for adaptive gardening and adaptive riding for people with dementia. More research is needed with a larger sample size to further examine similarities and differences.